An Investigation of the Current Autonomy Status of the Malaysian Public and Private Universities: An Empirical Result - Al-haimi, Basheer; Nasir Ibrahim, Daing; MR, Ab Hamid (KnE Social Sciences, 2019)
The benefits and importance of university autonomy for facilitating and accelerating higher education transformation have been broadly agreed by many higher education stakeholders. This paper aims to investigate the Malaysian public and private universities degree of independence and autonomy from the government and other external forces. The extent of an institute’s autonomy is measured based on their independent in appointive, academic, administrative, and financial matters. An emailed survey has been sent to top-level management of 28 public and private universities in Malaysia, resulting in 126 respondents. The respondents for the survey consisted of vice-chancellors, deputy vice-chancellors, deans, directors, and deputy deans. Using SPSS statistical software, data were analyzed by descriptive and inferential statistical analysis. The results demonstrate that the majority of the components under academic matters, administrative and financial matters are considered high autonomy, with less interference of the government over those institutions. With some reason, autonomy related to the appointment of the vice-chancellors and dismissals of rectors and vice-chancellors is still under government control. However, based on the findings, autonomy development at public and private universities in Malaysia has been engaged in a long journey that enabled it to compete and to progress well at the global level.